Prepartum Eculizumab for prevention of atypical hemolytic, Michela uremic syndrome: A case report. Issue 6 (2016) - Ardission, Gianluigi; Baffero, Giulia Maria; Ossola, Manuela Wally; Agnoli, Benedetta Maria; Tel, Francesca; Perrone, Michela; Salardi, Stefania; Sgarbanti, Martina; Tedeschi, Silvana
No abstract available